Efek Komunikasi Media Sosial pada Persepsi Konsumen Gen Z terhadap Merk Streetwear Fashion Lokal di Indonesia - Tan, Jones; Sachio, Ken; Ratna Tercia, Christiana Yosevina; Amelia, Novi (Universitas Prasetiya Mulya, 2023)
Previous studies link Instagram contents with impulsive buying behavior, by passing evaluation stages in buying process. This study aims to fill this gap by considering the consumer behavior process leading up to the emergence of purchase intentions. specifically, this research will examine the relationship between firm-created contents and user-generated contents with the purchase intentions of Gen Z consumers towards Erigo, while considering brand awareness, brand attitude, and belief in global brand citizenship. SEM-PLS analysis was conducted on 135 sample respondents through an online questionnaire, using the purposive sampling technique. This study resulted in two findings: (1) firm-created contents positively influences belief in global brand citizenship, consequently, positively affects Gen Z consumers' purchase intentions towards the Erigo brand, (2) user generated contents positively influences brand attitudes and beliefs in global brand citizenship, both of which, consequently, positively affect Gen Z consumers' purchase intentions towards the Erigo brand.